Emerging targeted therapies for melanoma treatment (Review) - Russo, Angela; Ficili, Bartolomea; Candido, Saverio; Pezzino, Franca Maria; Guarneri, Claudio; Biondi, Antonio; Travali, Salvatore; McCubrey, James A.; Spandidos Demetrios A.; Libra, Massimo (My University, 2014)
Cutaneous melanoma is an aggressive cancer with a poor prognosis for patients with advanced disease. The identification of several key molecular pathways implicated in the pathogenesis of melanoma has led to the development of novel therapies for this devastating disease. In melanoma, both the Ras/Raf/MEK/ERK (MAPK) and the PI3K/AKT (AKT) signalling pathways are constitutively activated through multiple mechanisms. Targeting various effectors of these pathways with pharmacologic inhibitors may inhibit melanoma cell growth and angiogenesis. Ongoing clinical trials provide hope to improve progression-free survival of patients with advanced melanoma. This review summarizes the most relevant studies focused on the specific action of these new molecular targeted agents. Mechanisms of resistance to therapy are also discussed.
Keywords: melanoma; MAPK/AKT pathway; targeted therapies